Harder-to-reach people living with HIV experiencing high prevalence of all-type mental health disorder diagnosis. Issue 6 (3rd June 2017) - Salters, Kate A.; Irick, Marina; Anema, Aranka; Zhang, Wendy; Parashar, Surita; Patterson, Thomas L.; Chen, Yalin; Somers, Julian; Montaner, Julio S. G.; Hogg, Robert S.
ABSTRACT: People living with HIV/AIDS (PHA) often concurrently cope with mental health disorders that may greatly influence HIV and other health-related outcomes. The objective of this study was to examine the prevalence and correlates of self-reported mental health disorder diagnosis among a cohort of harder-to-reach HIV-positive individuals in British Columbia, Canada. Between 2007 and 2010, 1000 PHA who had initiated ART were enrolled in the Longitudinal Investigation into Supportive and Ancillary health services (LISA) study. Socio-demographic, behavioral, health-care utilization and psychosocial information was collected through interviewer-led questionnaires and linked to longitudinal clinical variables through the provincial Drug Treatment Program at the BC Centre for Excellence in HIV/AIDS. We identified the prevalence of all-type and specific mental health disorders among this population. Of the 916 participants included in this analysis, 494 (54%) reported ever having a mental health disorder diagnosis. Mood (85%) and anxiety (65%) disorders were the two most frequently reported mental health conditions. Self-reported all-type mental health disorder was independently associated with decreased overall functioning (adjusted odds ratio [AOR] = 0.90, 95% confidence interval [CI] = 0.83–0.98) and life satisfaction (AOR = 0.81, 95% CI = 0.74–0.89), and having higher stigma score (AOR = 1.11, 95%CI = 1.02–1.21). Participants reporting any mental health disorder were more likely to report a history of sexual assault (AOR = 2.45, 95% CI = 1.75–3.43) and to have used case management services (AOR = 1.63, 95%CI = 1.17–2.27). Our findings uncovered a high burden of mental health disorders among harder-to-reach PHA and suggest that PHA with at least one mental health disorder diagnosis are disproportionately impacted by sexual violence and stigma.